Differences in Early Season Emergence and Reproductive Activity Between Spathius agrili (Hymenoptera: Braconidae) and Spathius galinae, Larval Parasitoids of the Invasive Emerald Ash Borer (Coleoptera: Buprestidae). Issue 2 (8th January 2020) - Ragozzino, Max; Meyer, Ryan; Duan, Jian; Slager, Ben; Salom, Scott
Abstract: Both Spathius agrili Yang and Spathius galinae Belokobylskij and Strazanac are host-specific parasitic wasps introduced for biological control of emerald ash borer in North America. Spathius agrili is native to northeastern China and S. galinae comes from a more northern, colder climate in the Russian Far East. Their origin may lead to differing abilities to adapt to climate and their host in North America. We conducted both field and laboratory experiments to determine the timing of early season emergence and synchronization of each parasitoid species to their host in the United States, and if manipulating prerelease conditions could affect emergence time. A cold acclimatization treatment prior to parasitoid emergence was assessed and compared with untreated control group reared with standard rearing protocols. Stands of naturally emerald ash borer-infested ash were sampled at two locations in Virginia throughout the experiment to determine when the parasitoid-susceptible life stage (third to fourth instar) occurred. Untreated S. galinae emerged approximately 2 wk earlier than any other cohort, whereas cold acclimatized S. galinae emerged later than any other cohort. Emergence time of S. agrili was unaffected by cold acclimatization. Cold acclimatization treatment did not affect the parasitism rate of either species, nor did it have multigenerational effects. Emergence time of the subsequent generation of S. agrili was delayed by cold acclimatization treatment, whereas S. galinae experienced no multigenerational effects. At Virginia field sites, susceptible EAB larvae were present during the emergence time of all four groups of parasitoids. Untreated S. galinae had the least overlap with any susceptible EAB larvae.